Effect of impurities content from minerals on phase transformation, densification and crystallization of α-cordierite glass-ceramic - Banjuraizah, Johar; Hasmaliza, Mohamad; Zainal Arifin, Ahmad (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com/